An Advanced Method for Sloving Fuzzy Transportation Problem with Robust Ranking Technique - G.Nagalak, R.Anandhi, B.Satheesh kumar, (International Journal of Scientific Research and Management (IJSRM), 2017)
An Advanced Method for Sloving Fuzzy Transportation Problem with Robust Ranking Technique